2003
DOI: 10.1080/00207450390231527
|View full text |Cite
|
Sign up to set email alerts
|

Brief Clinical Report: EVALUATION OF ANTIOXIDANT STATUS IN CHILDREN WITH ACUTE BACTERIAL MENINGITIS AND ENCEPHALITIS

Abstract: Antioxidant status was investigated in children with acute bacterial meningitis and encephalitis to investigate the possible role of free radicals in children with meningitis and encephalitis. Our study included 16 children with acute bacterial meningitis, 13 with encephalitis, and 17 control subjects. Serum ceruloplasmin, uric acid, albumin, bilirubin superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPx) levels were studied in all subjects within 6 h of admission. There was a statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…From the unchanged CAT levels, it can be speculated that CAT is not as effective as the GPx since the latter enzyme is much more active than the CAT in most antioxidant reactions. 29 Even though some investigators 24,25 and our present study revealed decreased SOD and GPx levels in pneumonia, our two previous studies 30,31 and those of Shukla et al 32 showed increased SOD, GPx and CAT levels in several infectious diseases such as meningitis, encephalitis, otitis media and tonsillitis. Similarly to Parks et al 33 and Aktan et al, 34 our present study showed that CAT levels remained unchanged in diseases such as experimental otitis media and pneumonia.…”
Section: Discussioncontrasting
confidence: 68%
“…From the unchanged CAT levels, it can be speculated that CAT is not as effective as the GPx since the latter enzyme is much more active than the CAT in most antioxidant reactions. 29 Even though some investigators 24,25 and our present study revealed decreased SOD and GPx levels in pneumonia, our two previous studies 30,31 and those of Shukla et al 32 showed increased SOD, GPx and CAT levels in several infectious diseases such as meningitis, encephalitis, otitis media and tonsillitis. Similarly to Parks et al 33 and Aktan et al, 34 our present study showed that CAT levels remained unchanged in diseases such as experimental otitis media and pneumonia.…”
Section: Discussioncontrasting
confidence: 68%
“…Their results indicate that SOD was locally produced in the middle ear [15]. In our previous study, all antioxidant activities except for albumin level were found increased in children with acute bacterial meningitis and encephalitis than those of control subjects [31].…”
Section: Discussionmentioning
confidence: 95%
“…The antioxidant species play an important role in numerous neurological diseases (Caksen, Dede, Cemek, Dulger, & Cemek, 2003). One of them, bilirubin (Bil), may reduce the risk of ischemic stroke (IS) possibly due to its powerful antioxidant properties (Perlstein, Pande, Creager, Weuve, & Beckman, 2008).…”
Section: Introductionmentioning
confidence: 99%